MENUJU MA’RIFATULLAH MENYELAMI SAMUDERA SUFISME IMAM AL-GHAZALI - AS, Asmaran (Jurnal Studia Insania, 2016)
Ma?rifatullah (knowing Allah) is a foundation of Islamic teaching because it is a vital part of Muslim?s  faithful. Other Teachings of Islam stand on it, because without the strong foundation such as knowing Allah sturdily, perhaps, the someone will not  do his obligation, or at least what he is doing doesn?t have any useful for himslef  as a pleasant of life nor for another people as a good behave in society. There is a question to be answerd: What is the nature of ma?rifatullah? In particular, This question deepens in sufism of Imam al-Ghazali toward Ma?rifatullah. Mentioned here toward Ma?rifatullah, because a Muslim is only able to know Allah as in accordance with his limited ability to Allah, who is unlimited. According to al-Ghazali, Ma?rifatullah means  convincing ?knowledge?. It happens if the object is uncovered clearly without any hesitations. It means revealed of the secrets of divinity and all secrets of His creations. This circumstance cannot be reached by senses of experience and or logical reasoning, but it is purely a gift or divine inspiration from God through nûr which is given to heart. Thus, it opens up all secrets are there behind this reality, which is not able to reach by someone?s sense and mind. The circumstance is called as mukâsyafah. At the time, someone i sable to know Allah through the manifestation of His creation. Imam al-Ghazali had told that ma?rifatullah is ?looking at Allah?s face?. Of course, it means looking at the visible manifestation of Allah traits in this universe.